Business Development Strategy through Product Diversification of Crispy Bitter Melon in the Reginda Crispy Mushroom Home Industry - Nur Faiqoh Izzati; Dumasari Lumongga; Muhammad Amir Biky; Watemin Watemin; Pujiati Utami (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze business development strategies through the diversification of crispy bitter melon products at Reginda Jamur Crispy Home Industry. This study was motivated by increasing competition in the snack business and changes in consumer preferences towards innovative food products made from local ingredients. The research method used was a mixed approach (qualitative and quantitative) with a case study method. Primary data was obtained through observation, in-depth interviews with business owners, and questionnaires distributed to employees. Data analysis was performed using SWOT analysis to identify internal and external factors, followed by Quantitative Strategic Planning Matrix (QSPM) to determine priority strategies. The results showed that Reginda Jamur Crispy Home Industry was in Quadrant I (aggressive strategy) with coordinates (0.69; 0.34). The priority strategy was to utilize the unique taste of pare crispy as a competitive advantage with the highest STAS value of 15.08. This strategy was considered capable of increasing business competitiveness and supporting business sustainability.